Function and therapeutic potential of transient receptor potential ankyrin 1 in fibrosis - Wei, Yicheng; Cai, Jialuo; Zhu, Ruiqiu; Xu, Ke; Li, Hongchang; Li, Jianxin (Frontiers in Pharmacology, 2022)
The Transient Receptor Potential (TRP) protein superfamily is a special group of cation channels expressed in different cell types and signaling pathways. We focus that TRPA1 (transient receptor potential A1) is one of ion channels in this family which exists in cell membrane and shows a different function with others TRP channels. TRPA1 usually has a special activation effect, which can cause cation ions to flow into activated cells, especially calcium ions. In this paper, we review the role of transient receptor potential ankyrin1 (TRPA1) on the fibroblasts. In order to clarify the relationship between fibroblasts and TRPA1, we also pay special attention to the interaction between TRPA1 and inflammatory factors leading to fibroblast activation. TRPA1 has different functions in the process of different organ fibrosis, and there is also an interesting discussion with the mechanism of TRPA1 and fibroblasts. Therefore, this paper is aimed to describe the function of TRP channels in controlling fibrosis through fibroblasts in different organ inflammation and immune-mediated diseases. We tried to prove that TRPA1 is targeted to fibrosis. At the same time, some clinical trials have further proved that TRPA1 is a potential adjuvant therapy for anti-fibrosis.